Authentication of edible fats and oils by non-targeted 13C INEPT NMR spectroscopy. (September 2018) - Guyader, Sophie; Thomas, Freddy; Portaluri, Vincent; Jamin, Eric; Akoka, Serge; Silvestre, Virginie; Remaud, Gérald
Abstract: Further to recent food scandals, consumers have become increasingly concerned about the quality and integrity of the processed products they buy and eat. Edible oils contaminations or deliberate adulterations are recurring issues. Until now the lipidic composition of food has not been extensively studied by Nuclear Magnetic Resonance (NMR) spectroscopy despite the fact that this analytical method can cover a wide range of matrices. The application of a refocused adiabatic 13 C INEPT (Insensitive Nuclei Enhanced by Polarization Transfer) sequence has already proved the performance of NMR spectroscopy to discriminate the origins of olive oils. This sequence has been demonstrated to be faster than a classical 13 C NMR sequence. In this work, the implementation of that 13 C NMR sequence in a routine laboratory has allowed the analysis of 23 common origins of edible oils, as well as butters, margarines and animal fats. We have proven that butter origin could clearly be distinguished from plant oil origins considered in this work. With the example of the verification of palm oil presence in food products, we have demonstrated the applicability of the method to characterize fats origin in transformed products. This study has shown by means of chemometric tools the potential of 13 C NMR spectroscopy to check the authenticity of various commercial finished products, using an untargeted approach applied to a spectral database of 294 spectra of raw animal and plant fats and oils. Thanks to spiking tests, the limit of detection of one origin of plant oil in another has been estimated as being around 5% and the limit of detection of animal oil in plant oils has been estimated as being around 2%. The same approach can be applied as a global method to verify the authenticity and integrity of fats and oils. Highlights: Edible oils contaminations or adulterations are recurring issues. 13 C NMR spectroscopy to check the authenticity by an untargeted approach applied to 294 spectra. Distinction of 23 common origins of edible oils, butters, margarines and animal fats. Applicability to characterize fats origin in transformed products.